Experienced CEO and Factor Productivity Improvement: Re-Examination of Experience Trap - Chengpeng Zhu; Mengyun Wu; Jie Xiong (Complexity)
We examine the role of experienced CEO in the CEO succession and their contributions to the performance of focal firms. We utilize the propensity score matching with difference in differences (PSM-DID) model to evaluate to what extent experienced CEO succession affects the total factor productivity (TFP) growth. Based on the analysis of 1,675 listed manufacturing companies in China, results show that experienced CEO in succession significantly improves firms’ TFP. Our analysis demonstrates that, on average, the event of hiring an experienced CEO succession yields a 3.1% increase in TFP improvement compared with nonsuccession firms. This positive effect can be continued for three years. Furthermore, the heterogeneous effect of experienced CEO succession on TFP is shown between different categories of focal firms (i.e., high-tech versus low-tech enterprises).